A Patient's Perception about Experience of a Root Canal Treatment: A Cross-Sectional Study - Athar Parvez, Rida Mujeeb, Noman Ali, Ahmed Chaudhry, Abdullah Karamat, Mujahid Rahman, (Pakistan Journal of Medical & Health Sciences, 2025)
Background and Aim: Root canal treatment (RCT) is considered as a painful procedure but is rendered as the most popular modality for any dental setting. The major concern for dental patients is the anxiety and pain encountered during RCT. The present study aimed to assess the patient’s perception regarding root canal treatment experience. Materials and Methods: This questionnaire based analytical cross-sectional study was carried out on 156 patients who experienced root canal treatment in the Department of Dentistry of a Tertiary Care Hospital of Lahore, Pakistan from January 2022 to December 2022. Respondents were given the opportunity to evaluate their feelings about the endodontic treatment both prior to and following the procedure. Demographic details, pain, anxiety associated with questions, and concern about RCT were recorded on a pre-validated questionnaire. Pre and post-test scores were compared using paired t-tests. Results: Out of the total 156 patients, there were 92 (59%) male and 64 (41%) female study participants. The overall mean age of male and female subjects was 22.48 ± 12.68 and 27.52 ± 8.32 years respectively. The current study analyzed the patient's anxiety level, which was shown to be considerably lowering from pre-treatment values of 30.54 ± 14.86 to post-treatment values of 22.32 ± 12.84 respectively. Similarly, the mean predicted and experienced pain score decreased dramatically from that of pre-treatment value of 40.12 ± 22.42 to 20.88 ± 14.46 post-treatment value. Conclusion: The present study found a substantial decrease in the mean anxiety score for RCT post-treatment. Furthermore, with the treatment, there was a considerable difference between predicted and realized pain. Prior to treatment, a considerable proportion of patients were unconcerned about RCT, rather the majority of patients were anxious about the pain associated with it (RCT). Keywords: Root canal treatment, Patient’s perception, Anxiety, Pain, Endodontics.